Possible effects of pramipexole on neck muscles in a patient with Parkinson's disease. Issue 1 (5th April 2014) - Filippi, Roberto; Rasetti, Mario; Lenzi, Marco; Bright, Peter
Abstract: Recent case reports suggest a possible causal correlation between antecollis and pramipexole. Here, we report the case of a 62-year-old Italian man with a 2-year history of Parkinson's disease (PD) and cervical spondylosis for which he was treated with pramipexole. He developed severe neck rigidity immediately after an inguinal hernia operation but several months after introduction of pramipexole. He was initially treated with painkillers and physiotherapy with no significant improvement. His condition deteriorated presenting disproportionate rigidity between anterior and posterior neck muscles (antecollis) to the extent that normal activities were severely restricted. However, significant improvement occurred after the withdrawal of pramipexole. The patient undertook a second cycle of physiotherapy with remarkable results and returned to function normally in everyday life. This case report suggests that neurologists should be motivated to inform the scientific community about other possible cases in which an association between antecollis and pramipexole might operate in PD.